What is Supervision? The Views of Child and Family Social Workers and Supervisors in England. Issue 4 (8th August 2022) - Pitt, Charlotte; Addis, Samia; Wilkins, David
Abstract : The importance of supervision is largely taken for granted within social work. Yet it can often seem as if policy-based descriptions of what supervision 'should be' are disconnected from the realities of practice. In this study, we sought to understand the perspectives of social workers and supervisors about what supervision is and what it is for. Interviews were undertaken with social workers (n = 56) and supervisors (n = 10) in one authority in England between September 2018 and March 2019. We identified three functions of supervision – accountability, emotional support and providing a different perspective. Supervisors were expected to be constantly available for their staff yet had insufficient time to engage in what they considered to be reflective discussions. Supervision was considered to be primarily a mechanism for worker accountability, with support and education being much more ad-hoc functions. These findings suggest that while workers are not wholly negative about case management approaches to supervision, there is a pressing need to define reflection more clearly and articulate what it looks like in practice and how else, if not via supervision, it can be enabled within statutory services for children and families.